Optimization of Packaging and Marketing Strategies for Micro, Small, and Medium Enterprises (MSMEs) of “Cap 2 Udang” Shrimp Paste in Paciran Lamongan - Mutiara Aisyah Nur Rahmah; Mar’atus Tsania; Hanum Salsabila Hassa; Silfiana Silfiana; Naslizah Naslizah (CV. Dharma Samakta Edukhatulistiwa, 2026)
Micro, small, and medium enterprises (MSMEs) engaged in seafood processing play an important role in strengthening the economy of coastal communities. However, issues related to packaging quality and the use of digital marketing remain obstacles to improving product competitiveness. The Terasi Cap 2 Udang MSME, located in Paciran District, Lamongan Regency, shows a gap between the theoretical concept of the importance of packaging and digital promotion and the actual conditions in the field, where product packaging is not yet optimal and digital promotional content is still simple. This community service activity aims to optimize packaging quality and strengthen the digital marketing strategy of MSMEs through a participatory assistance approach. The method of implementation consists of three stages, namely preparation, implementation, and evaluation. The preparation stage is carried out through field observations, interviews, and business problem analysis. The implementation stage was carried out through mentoring on product packaging aspects and the development of digital promotional content in the form of product videos. The evaluation stage was carried out by observing changes in packaging quality, packaging process efficiency, and consumer responses to digital promotions carried out through social media. The results of the activities show an increase in the neatness and uniformity of product packaging, an increase in partners' understanding of digital marketing, and increased consumer attention to products. Overall, these mentoring activities have had a positive impact on increasing product competitiveness and supporting the sustainability of MSME businesses in coastal areas.